(untitled) (Andamios, Revista de Investigación Social, 2026)
Describing the body from a feminist perspective entails a theoretical, political and epistemological journey that has been central to feminist theory, research and activism. Drawing on communication studies, we resume the expressive and symbolic dimensions of the body to analyze, from a situated, feminist, and autoethnographic approach, how it is configured as a communicative vehicle in visual practices. Based on the textile project “embroidering to heal” and the community photography experience with Mujeres por la Memoria de Cherán (Women for Memory of Cherán), we show that feminist embroidery and photography operate as devices for naming pain, producing embodied memories, weaving networks of care and challenging hegemonic narratives about women’s bodies.